PENGEMBANGAN STRATEGI DIGITAL MARKETING BAGI UMKM : MENINGKATKAN POTENSI BISNIS ES TEH KITA INDONESIA - Muslinawati, Retno; Aziz, Khalid Fauzi; Arifin, Putri Autika; Putri, Yustika Arida (Jurnal Abdi Masyarakat, 2025)
The underlying problem of mentoring SMEs in Bojonegoro Regency is the low ability of SMEs to utilize digital technology for marketing, which results in limitations in reaching a wider market and increasing competitiveness. The goal of this mentoring is to improve the digital marketing competency of SMEs, so they can compete effectively in the digital era. The scientific contribution from this community service is expected to enrich knowledge about the application of information technology in marketing and provide new insights in developing digital-based business strategies. The methods used in this mentoring include training, technical guidance, and the implementation of effective digital marketing strategies. The results of the mentoring show a significant increase in SMEs' understanding of online marketing, as well as increased product sales through digital platforms. Targets achieved include an increase in the number of customers and a 30% increase in sales turnover within the three-month period following the training. Thus, this mentoring not only provides direct benefits to partners but also contributes to the overall development of SMEs in Bojonegoro Regency.